Market Orientation's Boundary‐Spanning Role to Support Innovation in SMEs. (27th October 2016) - Didonet, Simone Regina; Simmons, Geoff; Díaz‐Villavicencio, Guillermo; Palmer, Mark
Abstract : This study aims to examine the relationship between market orientation, sources of innovation and intra‐firm mechanisms to support innovation. A research conducted among 325 small and medium enterprises (SMEs) reveals that market orientation significantly affects sources of innovation, providing a market‐centric focus for SMEs. It also reveals that sources of innovation positively affect intra‐firm mechanisms for innovation. Finally, it reveals that market orientation has an indirect and positive effect on intrafirm mechanisms for innovation via the extent to which the studied SMEs use different sources of innovation. To better understand these relationships we consider market orientation's boundary‐spanning role for SMEs.